Analysis of vegetative homeostasis state of elite handball players - Prystupa, Y. N.; Tyshchenko, V. O. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to study characteristics and dynamic of elite handball players` physiological indicators. Material: In experiment elite handball players (n=112, age 18-35 years) participated. For determination of vegetative homeostasis state we analyzed variability of heart rhythm. The researches were conducted in laboratory conditions in rest state, in lying position during 5 minutes. Results: it was found that organism`s adaptation reactions to training loads go with different tension of regulation systems. At the end of competition period there appears hyper-kinetic syndrome. It witnessed insufficiency of means, which permit to maintain optimal regulation of cardio-vascular system and increase its functional potentials. Conclusions: indicators of cardio-vascular system and their dynamic witnessed maintaining of high level of handball players` organism hemodynamic provisioning. High level of vegetative homeostasis pointed at certain degree of sportsmen`s fitness. Such state is sufficient for preservation of high potential of sympathetic -adrenaline system and overcoming of fatigue processes.